Ações colaborativas em contexto escolar: desafios e possibilidades do ensino de química para alunos com deficiência visual - Melo, Érika Soares de (2013)
This research intends to promote collaborative actions between a Chemistry teacher and a Special teacher of a school which is reference in attending visually impaired students from the inner part of the state of São Paulo, taking into account school inclusion and teaching-learning in Chemistry. The field research was developed in a state school of the inner part of the state of São Paulo, in the first year of High School. The research subjects were: a Chemistry teacher, a Special teacher and four students with visual impairment. The research was guided by the collaborative critical action research, which aims to contribute to the continuing education of the professionals in their work context and focus on possible reflections which may emerge in the process of rethinking their teaching practices. The data collection was divided into different steps: semi-structured interviews, in order to know the professional journeys of the Chemistry teacher and the Special teacher and also to know the visually impaired students school careers; coordinated meetings with the Chemistry teacher and the Special teacher, to promote collaborative actions and to develop pedagogical practices for teaching Chemistry to students with visual impairment; classroom observations, to understand the possibilities and tensions in the intervention using inclusive pedagogical practices with the visually impaired students; and classroom intervention, which would allow the teacher to try the pedagogical practices which were proposed in the meetings. The results showed how the Chemistry teacher cared about her students, since she had never taught students with visual impairment before. The partnership between the Chemistry teacher and the Special teacher was positive, culminating in the adaptation of materials for classroom intervention, which made the VI students get better grades in the evaluations. The students were evaluated considering their organization and participation in the School Science Fair and they did a very good job, being praised by the fair visitors. The bimonthly tests were also considered in the evaluation and it was observed that there are some obstacles to be overcome by the school and the students with visual impairment.